Stereotactic body radiation therapy (SBRT) on renal cell carcinoma, an overview of technical aspects, biological rationale and current literature. (November 2018) - Francolini, G.; Detti, B.; Ingrosso, G.; Desideri, I.; Becherini, C.; Carta, G.; Pezzulla, D.; Caramia, G.; Dominici, L.; Maragna, V.; Teriaca, M.A.; Bottero, M.; et al.
Abstract: Background: Stereotactic body radiotherapy (SBRT) is characterized by the delivery of high doses of ionizing radiation in few fractions. It is highly effective in achieving local control, and, due to the high biological effective dose administered, it seems to overcome the radioresistance of renal cell carcinoma (RCC). Thus, SBRT could constitute a treatment option for the management of localized RCC in patients who are not surgical candidates. In this paper, we report an overview about data from the current evidence about SBRT in patients affected by localized RCC. Materials and methods: A non-systematic review was performed, including data from both retrospective and prospective studies focusing on the use of SBRT for localized RCC and its biological rationale. Furthermore, ongoing trials on this issue are reported. Conclusion: Currently, SBRT might be considered a treatment alternative in inoperable patients affected by primary RCC. Currently, dose-escalation to 48 Gy in 3–4 fractions are effective and well tolerated. Emerging role of immune therapies in RCC patients warrant further studies to explore interactions between SBRT and immune response.